Shawn O'Brien: Manslaughter - Book 2 - Johnstone, William W.; Johnstone, J. A. (New York, NY : Pinnacle Books, 2015)
"In Broken Bridle, Wyoming, Jeremiah Purdy, the towns tinhorn sheriff is a college kid who wants to become governor some day. But outlaw Burt Becker couldnt care less about anyone elses ambitions. With Becker holding Broken Bridle in a bloody grip of terror, Purdy sends a desperate cry for help--to Shawn OBrien, town tamer."--
Keywords: Outlaws -- Fiction; Wyoming -- Fiction; Western fiction